(3GdebGdI GdYeGOjI aj MaX GdUMI GdHOfjI hOaY GdCSHGH GdeQVjIs - (3CHh HcQ Hf jhSa Hf OGhO GdefLe GdeYQha HGdeMdGhj, GdeMdGhjs
(3ChdgG (B:s
(3GSe jGeHOY GdcGFfGJ hechf GdeQcHGJ hHYO aCbhd Efg deG JUObJ Ydi GdbOQI GdEdgjI HGdfbdI YeG cfJ Ydjg Edi GdUfGYI GdfLhejI s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg hcfJ ejSJQ adG ZjQ GdePd ceG bO cGf PG HSWI ai GdfGS s
(3fSNI NRGFfjIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs